Islamic banking spin-offs decision: A bibliometric review - Zulfikar Bagus Pambuko; Jaka Sriyana (Cogent Business & Management, 2023)
The purpose of this study was mapping the future research path by determining the progress of literature on spin-off decisions in Islamic banking from 1:2012 to 5:2022. The analysis, however, was limited to the author, source, and keywords. Scopus, Dimensions, and Google Scholar are some of the databases utilized for this bibliometric analysis. The inclusion criteria were English articles on spin-off decision in Islamic banking in the form of journal articles and proceeding papers. Biblioshiny R-package and VOSviewer software were used to analyze a total of 63 publications. Our investigation indicates that studies focusing on spin-off decisions in Islamic banking grew at a 23.08 percent annual rate during the years of observation. This study involved 117 authors where MNR Al Arif from UIN Syarif Hidayatullah Jakarta was a prolific author with 11 publications (h-index 8). Furthermore, when compared to other journals, Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah publishes the most papers. The study of spin-offs is most popularly studied in Indonesia, considering that those are the main development strategy for Islamic banking. Popular keywords in this topic relate to banking performance, such as profitability, liquidity and efficiency. As a result, researchers are focusing their efforts on determining the impact of spin-offs on the performance of Islamic banks although there is no consensus so far. The investigation also provides an overview of the future agenda.
Keywords: 650; Bibliometric review; Biblioshiny; Islamic banking; Spin-off decision; Vosviewer